Aspects of Federalism Implementation for Development and Prosperity - Rapacha, Lal (Molung Educational Frontier, 2018)
In Nepal‘s context, concepts like 'development' and 'prosperity' are two age-old (suppressive Rana oligarchy, uni-Panchayat regime and its aftermath) mirages chased by rulers for the ruled ones almost seem to be unattainable. Nevertheless, the mirages of 'development' and 'prosperity' can be materialized when one readily changes his/her antediluvian attitude of fatalism (Bista 1991) and low work ethics. In a recent political paradigm shift from unitary monarchism-oligarchy to multi-party federalism, those two mirages have again been reiterated as Nepalese people's dream and discourse (claimed as Oli-vision) in political arena. In our recent practice, federalism is in its infancy and as a form of government may not matter much first about separating or devolution of political power more effectively, avoiding the power concentration and bringing government responsibilities closer to the citizens. In fact, what acutally matters is its action-oriented effective implementation for separating 'development' from 'fatalism' before it turns frequently into a vicious nightmare. Thus, this paper aims to explore some pertinent aspects or preconditions/hindrances of implementing federalism effictively for achieving the aforesaid goal of 'development' and 'prosperity' within our prevalent general socio-political and bureaucratic trend of 'Balaram syndrome' (a metaphor of ethical degradation of mankind), 'bholi' and 'chiya' syndrome, 'sida-bida' syndrome, nepotism, cronyism, medieval mindset, malpractices of blind capitalism and absence of good governance. In this paper, my main point of departure in methodological tool as such is a closer observation of socio-political trends in Nepalese society and its relevant literature.